Study of serum lipid profile and serum lipo-protein (a) in type II diabetes mellitus patients compared to non-diabetics - Rao, J. Prathyusha; Thota, Abhinav (International Journal of Advances in Medicine, 2021)
Background: This study helps us in evaluating present Indian scenario of lipid and diabetic portfolio, and advices about how aggressive treatment should be for immediate control of blood sugars and lipids are to minimize the cardiovascular risks. The objective of this study was to evaluate the serum lipid profile and lipo-protein (a) levels in comparison to patients with type II diabetics with non-diabetics. Methods:It was a hospital-based case control study conducted on patients presenting with signs and symptoms of diabetes mellitus and confirmed on doing appropriate investigation. 200 patients of which 100 were non-diabetic (control) and 100 type II diabetic patients, of which fifty were type II diabetics were on oral hypoglycemic agents (OHA) and 50 were on insulin only, were selected after matching for age and sex. Lipid profile, serum lipoprotein (a), ECG, 2D echo was studied in these patients. Results: The males were more (74%) than females (26%) among the cases. Fasting blood sugar, post prandial blood sugar and HbA1c were significantly more in cases. Triglycerides, LDL, VLDL and lipoprotein (a) were significantly more in cases. ST shift (mm) and T wave inversions were significantly more in cases compared to controls (p<0.05). Mean ejection fraction was significantly reduced in cases compared to controls. FBS and PPBS were not significantly different in two groups of OHA and insulin but HbA1c was significantly better controlled in insulin group than OHA group. Conclusions:Lipid profile and lipoprotein (a) as well as ECG and 2D echo parameters were significantly worse in diabetes patients. Hence appropriate management is important to prevent risk of complications.